2023
DOI: 10.3390/foods12040725
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Omega-3 Fatty Acids Supplementation on Serum Lipid Profile and Blood Pressure in Patients with Metabolic Syndrome: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: The purpose of this study was to explore the effect of omega-3 polyunsaturated fatty acids (n-3 PUFAs) supplementation on serum lipid profile and blood pressure in patients with metabolic syndrome. We searched PubMed, Web of Science, Embase, and the Cochrane library from database inception to 30 April 2022. This meta-analysis included eight trials with 387 participants. We found that supplementation of n-3 PUFAs has no significant reduction in TC level (SMD = −0.02; 95% CI: −0.22 ~ 0.18, I2 = 23.7%) and LDL-c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 50 publications
1
6
0
2
Order By: Relevance
“…Simonetto et al, in a publication, indicated that omega-3 PUFA supplementation may reduce the risk of various phenotypes of atherosclerosis and cardiovascular diseases [134]. A 2023 systematic review indicated and confirmed that omega-3 also improves the blood lipid profile [135]. The cardioprotective effect of omega-3 fatty acids is therefore firmly established in the literature and further confirmed by a number of recent publications, including meta-analyses [136][137][138][139][140].…”
Section: Anti-inflammatory Cardioprotective Effects Of Omega-3 Fatty ...mentioning
confidence: 90%
“…Simonetto et al, in a publication, indicated that omega-3 PUFA supplementation may reduce the risk of various phenotypes of atherosclerosis and cardiovascular diseases [134]. A 2023 systematic review indicated and confirmed that omega-3 also improves the blood lipid profile [135]. The cardioprotective effect of omega-3 fatty acids is therefore firmly established in the literature and further confirmed by a number of recent publications, including meta-analyses [136][137][138][139][140].…”
Section: Anti-inflammatory Cardioprotective Effects Of Omega-3 Fatty ...mentioning
confidence: 90%
“…Consumir uma quantidade adequada de ômega-3 pode prevenir a hipertrigliceridemia ao inibir a produção hepática de triglicerídeos e lipoproteínas de baixa densidade (SCORLETTI, BYRNE, 2018). Além disso, o ômega-3 influencia positivamente a saúde metabólica, afetando processos como a adipogênese e a expansão saudável do tecido adiposo (LIU et al, 2023).…”
Section: Ensaios Clínicosunclassified
“…Em um estudo que utilizou óleo de canola rico em et al, 2021). Revisões sistemáticas indicam que os efeitos do ômega-3 são mais evidentes em intervenções de longo prazo, com uma redução significativa dos níveis de triglicerídeos após 12 semanas ou mais (LIU et al, 2023). Esses resultados sugerem que a duração da intervenção desempenha um papel crucial nos efeitos do ômega-3 no perfil lipídico, com benefícios mais pronunciados se estendendo ao longo do tempo.…”
Section: Ensaios Clínicosunclassified
“…Salvia hispanica seeds are rich in essential fatty acids (81%), including α-linolenic acid (ALA, ω-3, 62%) and linoleic acid (LA,19%) with low ω-6:ω-3 ratio (0.3), which makes it one of the best sources of plantbased ω-3 (Oteri et al, 2023). Several studies examining the effect of ω-3 polyunsaturated fatty acids (ω-3-PUFAs) supplementation on human health suggest that they may help reduce several chronic diseases such as diabetes, cardiovascular and inflammatory disorders, hypertension, dyslipidemia, and kidney dysfunction (Arredondo-Mendoza et al, 2020;Creus et al, 2017;El-Feky et al, 2022;Y.-X. Liu et al, 2023;Meyer & De Groot, 2017;Ong et al, 2023;Onneken, 2018;Penson & Banach, 2020;Y.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies examining the effect of ω‐3 polyunsaturated fatty acids (ω‐3‐PUFAs) supplementation on human health suggest that they may help reduce several chronic diseases such as diabetes, cardiovascular and inflammatory disorders, hypertension, dyslipidemia, and kidney dysfunction (Arredondo‐Mendoza et al., 2020; Creus et al., 2017; El‐Feky et al., 2022; Y.‐X. Liu et al., 2023; Meyer & De Groot, 2017; Ong et al., 2023; Onneken, 2018; Penson & Banach, 2020; Y. Xiao et al., 2022; X. Zhang et al., 2022).…”
Section: Introductionmentioning
confidence: 99%